If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 + x = -2 Solving -8 + x = -2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + x = -2 + 8 Combine like terms: -8 + 8 = 0 0 + x = -2 + 8 x = -2 + 8 Combine like terms: -2 + 8 = 6 x = 6 Simplifying x = 6
| 9x^2+26x+20=0 | | 15(x/4)= | | 5(3-d)+2=2 | | 7(3-m)-11=-4 | | 11=-4+7e+9-e | | x-x=1-1 | | 15+3w+12+w=3 | | 4=3y-5 | | 4(y)-9-6(y)=2(y+5)-3 | | 6(3x+1)+5(10-4x)=39 | | 27x^2+9x+1=0 | | 9x^2+27x+1=0 | | (2x-6)x(-2)=0 | | ((2x-14)/(x^2-49))*((x^2+7x)/4(x-x^2)) | | (-2a^2+8a-8)/(16+8a^2) | | 4y+3x-5=y+2x+3y-4 | | 25g-4=54-2g | | 0.05=x/2 | | 5x-4/1-2+17x-20 | | 10a^2-3ab-b^2=0 | | 3x^2+7xy+2y^2=0 | | 6m^2+mn-2n^2=0 | | 4a^2-9ab-9b^2=0 | | (m-3)(m-3)=25 | | 6m^2+7mn+n^2=0 | | 65+20y+4x^2+4y^2=28x | | 1z+5=-21 | | 3x/x-2-4=14-4x/x-2 | | 3y^2+2yz-z^2=0 | | m/3(m+1)=3 | | -9+3n+10y-8y-6n+15= | | 4x^2/25*25/x^2 |